Constructing 3D interaction maps from 1D epigenomes - Yun Zhu (Nature Portfolio, 2016)
The human genome is highly organized, with one-dimensional chromatin states packaged into higher level three-dimensional architecture. Here, the authors present EpiTensor that can identify 3D spatial associations from 1D epigenetic information.